How Do Perceived Risk, Financial Transparency, and Platform Reputation Drive Investment Decision in Equity Crowdfunding in Indonesia? - Khanza Monica Salsabila; Dian Prawitasari; Herry Subagyo; Suhita Whini Setyahuni (International Journal Business, Management and Innovation Review, 2025)
With the growing popularity of equity crowdfunding as a business financing alternative, it is very important to understand the factors that are able to influence investment decisions.  This study aims to analyze the effect of perceived risk, financial transparency and platform reputation on investment decisions in equity crowdfunding in Indonesia. Using a quantitative approach and a purposive sampling technique, a total of 127 equity crowdfunding investors were surveyed. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results show that the three variables examined in this study, namely perceived risk, financial transparency, and platform reputation show a positive and significant influence on investment decisions. The findings can help equity crowdfunding platforms build trust and attract more investors by addressing concerns related to risk, transparency, and reputation. In turn, this contributes to broader financial inclusion, improved MSME access to funding, and the sustainable development of Indonesia’s digital financial ecosystem.